Fifteenth-Century Irish Provincial Legislation and Pastoral Care - Burrows, Michael A. J. (Studies in church history, 1989)
It is rewarding, if usually fairly difficult, to discover to what extent the views of medieval bishops on matters of devotion and church discipline impinged upon the spiritual lives of ordinary lay people. In the case of Ireland, provincial legislation probably provides the best available means by which to attempt this. Although the most important pastoral relationship within the Church was always that of priest and people in the parish, both parties were under the guiding hand and oversight of the bishop. It is to this ancient episcopal role as overseer, in die pastoral context, that the surviving sources direct us most.